2019
DOI: 10.1080/00219266.2019.1643761
|View full text |Cite
|
Sign up to set email alerts
|

Beauty, memories and symbolic meaning: Swedish student teachers´ views of their favourite plant and animal

Abstract: In the twenty years since the first theory of 'plant blindness' was published much discussion has ensued concerning this phenomenon. More recent research, not only demonstrates that humans appear to favour animals over plants but also indicates a preference for mammals with forward-facing eyes. For this paper, we analysed answers to an online survey conducted with 202 student primary teachers in Sweden collected over a period of two years. We focus on two open-ended questions concerning favourite plant and ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
2
14
0
2
Order By: Relevance
“…( The clear and consistent message from the global community of educators and scientists is that poor awareness of, or indifference to, the fundamental significance of the phytosphere is a persistent obstacle to environmental balance, and consequently the achievement of SDGs. This makes the need to address disdain of plants a vital issue for the scientific community and policy makers, and confirms education as the main social process for bringing about the necessary changes in perception and understanding; although with a caveat, as Nyberg et al (2019a) note:…”
Section: Sustainability In An Era Of Plant Blindness Is Unsustainablementioning
confidence: 87%
See 1 more Smart Citation
“…( The clear and consistent message from the global community of educators and scientists is that poor awareness of, or indifference to, the fundamental significance of the phytosphere is a persistent obstacle to environmental balance, and consequently the achievement of SDGs. This makes the need to address disdain of plants a vital issue for the scientific community and policy makers, and confirms education as the main social process for bringing about the necessary changes in perception and understanding; although with a caveat, as Nyberg et al (2019a) note:…”
Section: Sustainability In An Era Of Plant Blindness Is Unsustainablementioning
confidence: 87%
“…One of the issues in this area is the research methods and tools by which we evaluate what the educational challenges are (Balas and Momsen, 2014), which disciplines are engaged in the research (e.g. psychology, education, biological science, philosophy) and indeed, how populations vary in their connections with plants, particularly when considering emotional and aesthetic relationships (Nyberg et al, 2019a) in diverse cultural and climatic contexts. Several studies have confirmed that curriculum representations and coverage are a factor in the challenges teachers face when endeavouring to make the importance of plants more public (Amprazis and Papadopoulou, 2018).…”
Section: State Of Botanical and Ecological Educationmentioning
confidence: 99%
“…Hur man kan arbeta för att undvika människors oförmåga att uppfatta växter i den omgivande miljön, s.k. växtblindhet (plant blindness) (Wandersee & Schussler, 1999) och istället öka förmågan att verkligen se växter och deras betydelse för livet på jorden är en aktuell forskningsfråga (Calvo, Gagliano, Souza & Trewavas, 2020;Nyberg, Brkovic & Sanders, 2019;Sanders, 2019).…”
Section: Att Utforska Trädens LIVunclassified
“…växtblindhet (jfr. Nyberg et al, 2019;Sanders, 2019). Vid barnens utforskande av trädens livscykel i relation till årstiderna uppstod under projekttiden ständigt nya kopplingar som i sin tur öppnade för ytterligare frågor.…”
Section: Sammanfattande Diskussionunclassified
“…Knowledge acquisition requires a certain balance between what is rational or cognitive and what is affective-emotional [1][2][3]. However, our education system focused mainly on the development of the rational mind, identifying this with scientific knowledge [4].…”
Section: Introductionmentioning
confidence: 99%